2023
DOI: 10.3960/jslrt.22038
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of prednisolone alone in nodal peripheral T-cell lymphoma with T follicular helper phenotype

Abstract: A 71-year-old Japanese man presented with severe thrombocytopenia. A whole-body CT at presentation showed small cervical, axillary, and para-aortic lymphadenopathy, leading to suspicion of immune thrombocytopenia due to lymphoma. Biopsy was difficult to perform because of severe thrombocytopenia. Thus, he received prednisolone (PSL) therapy and his platelet count gradually recovered. Two and a half years after PSL therapy initiation, his cervical lymphadenopathy slightly progressed without other clinical sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Our findings corroborate this statement, as our study revealed that patients with nTFHL-NOS exhibited milder clinical manifestations, fewer laboratory and imaging abnormalities, less advanced-stage disease, and improved treatment response and survival. Furthermore, several case reports have substantiated these findings (17)(18)(19)(20)(21). Despite the absence of significant differences in clinical features between nTFHL-AI patients and nTFHL-F patients as well as nTFHL-NOS patients, patients with nTFHL-F exhibited worse survival outcomes, possibly indicating a more unfavorable prognostic subtype.…”
Section: Discussionmentioning
confidence: 80%
“…Our findings corroborate this statement, as our study revealed that patients with nTFHL-NOS exhibited milder clinical manifestations, fewer laboratory and imaging abnormalities, less advanced-stage disease, and improved treatment response and survival. Furthermore, several case reports have substantiated these findings (17)(18)(19)(20)(21). Despite the absence of significant differences in clinical features between nTFHL-AI patients and nTFHL-F patients as well as nTFHL-NOS patients, patients with nTFHL-F exhibited worse survival outcomes, possibly indicating a more unfavorable prognostic subtype.…”
Section: Discussionmentioning
confidence: 80%